Callus and cell suspension culture of Chelidonium majus L (Mongolian Journal of Agricultural Sciences, 2014)
Chelidonium majus L has long history as a being useful for the treatment of many diseases in Asian and European countries. Aim of this study is to cultivate callus and cell suspension culture in vitro using plant phytohormones. The proliferative capacity was tested on shoot and root explants, cultivated on Murashige-Skoog basal medium testing two auxins: 2,4-diclorphenoxiacetic acid (2.4D) and napheteline acetic acid in combination with cytokinine: kinnetine (K). Calluses were developed on MS medium with 0.5 mg/l Kin, 0.5 mg/l IAA from root explants, as well when added with 0.5 mg/l NAA and 0.5 mg/l Kin from shoot explants. More biomass of cell suspension culture of shoot and root callus was accumulated on MS medium added with 0.1mg/l Kin. DOI: http://dx.doi.org/10.5564/mjas.v11i2.238 Mongolian Journal of Agricultural Sciences Vol.11(2) 2013 pp.150-154